Religious Call in Eastern Orthodox Spirituality: A Theo-Phenomenological Approach - Nicolae Turcan (Religions, 2020)
Drawing a clear line between phenomenology and theology remains a challenging endeavor. This article has two parts: The first one argues that, from a methodological point of view, there is a need for a theo-phenomenology, a phenomenology which acknowledges religious faith as a given. The second part of the article tries to present the essence of religious call in Eastern Orthodox spirituality. Using ideas such as appeal and communion, divine grace, love, prayer, fidelity, apophatic intentionality, and a hyper-intelligible gaze before the Revelation, I will describe the phenomenon of religious call—God calling man and man calling God. The conclusion shows that religious call and answer are existential and theandric experiences, where one can work on askesis, the fidelity of thought, and mystical experience. Life in the Holy Spirit no longer distinguishes between call and answer for one who became a son of God by grace, faith, and good works.